Modern Full-Stack development : using Typescript, React, node.js, Webpack, and Docker - Zammetti, Frank W. (Apress, 2020)
Chapter 6: A Few More Words: Advanced TypeScript -- Interfaces -- Argument/Object Interfaces -- Methods in Interfaces -- Interfaces and Classes -- Extending Interfaces -- Namespaces and Modules -- Namespaces -- Modules -- Decorators -- Decorator Factories -- Third-Party Libraries -- Debugging TypeScript Apps -- Source Maps -- Summary -- Chapter 7: Tying It Up in a Bow: Webpack -- What's a Bundle, and How Do I Make One? -- What's Webpack All About? -- Dependency Graph -- Entry -- Output -- Loaders -- Plugins -- Modes -- Browser Compatibility -- Getting Started with Webpack